Influence of contract farming system on farmers' pest management practices: the case of vegetable growers in Malaysia - Abu Baka, Halimatunsadiah; Mazlan, Norida; Omar, Dzolkhifli; Kamarulzaman, Nitty Hirawaty (Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2015)
Farmers’ behavior on pesticide usage in vegetable farm productions is become one of the major attention in the food safety field. Due to misuse of pesticide and the application of high toxicity pesticides by farmers in farm productions, many environmental and health issues have been arisen regarding to the pesticide safety risk in fresh vegetables. Through the modern food supply chains, the introduction of contract farming system was believed to be able to reduce food safety risk related to the pesticide residue due to the stringent requirements specified by the downstream processors. In the study, a survey was conducted to identify the impact of contract farming system on farmers’ pest management practices in vegetable productions. Out of 150 respondents, only 21 farmers are found to be involved in contract farming. Study revealed that the integrated pest management (IPM) approaches practicing by majority both of contract farmers and non-contract farmers are very low as they still solely relied on synthetic pesticide usage to overcome pest and disease problems. It was found that there is no significant difference of pesticide spray frequency and pre-harvest interval (PHI) between contract and non-contract farmers. In overall, it was discovered that there was no great influenced of contract farming system towards the safe use of pesticides by vegetable growers in their pest management practices.